A study on the bridal gown preference of selected women from Quezon City and Batangas City - Malabanan, Shirley A. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT For a bride, one of the most important and exciting part is the selection of her wedding gown. Choosing a wedding gown can be very easy or very difficult, depending on whether the bride has an exact idea of the style she wants and what her budget is for the gown. This is a descriptive study that was done in order to give an insight on the bridal gown preference and budget of brides-to-be in Quezon City and Batangas City. This undergraduate thesis determined the selected respondents? choice of bridal gown and if their choice is affected by age, personal monthly income and area of residence. This research hoped to provide prospective brides, designers and dressmakers with a source of ideas and inspiration for bridal gowns. The study was able to provide a profile on the bridal gown preference of women from Quezon City and Batangas City that would help fashion designers in their bridal gown designs. The research also gives insights to future Clothing Technology students who may want to pursue the same topic. Quantitative research was employed in the study, facilitated by the use of a survey questionnaire that was prepared by the researcher. The questionnaires were distributed to one hundred (100) respondents who were selected through stratified random sampling. Fifty (50) respondents each from Quezon City and Batangas City were selected among those who attended the family planning seminar. The data collected from the survey were tallied and analyzed through frequency and percentage distribution. It was found that the most preferred silhouette is the fitted silhouette. The most preferred garment details are the basque waistline and strapless neckline. Most of the respondents prefer sleeveless gowns. The study revealed that bridal gown preferences vary among different ages and income. However, location is not a factor that affects the choice of bridal gown. It was also found that majority of the respondents shared that they are willing to spend P10,000 and P19,999 for their bridal gown. The respondents from Batangas City have higher budgets for bridal gowns compared to the Quezon City respondents. Majority of the Batangas City respondents are willing to spend P20,000 ? 29,999 for their bridal gowns while more Quezon City respondents are willing to spend P10,000 ? 19,999 for their bridal gowns. It is recommended to use a larger sample population for the survey to achieve a more conclusive study. Other locations and demographic parameters may also be studied for better comparison. Also, it is recommended to consider the respondents? figure types, personality and attitude in bridal gown selection to better understand the factors that would relate to the selection of bridal gowns by brides-to-be.